Quantitative profiling of bacteriocin present in dairy probiotics preparation of Lactobacillus pentosus by liquid chromatography mass spectrometery - Verma, Garima; Virk , Verinder (Journal of Postharvest Technology, 2022)
Bacteriocins are a heterogeneous group of ribosomally synthesized peptides or proteins with antimicrobial activity, produced predominantly by  lactic acid bacteria, with potential applications as biopreservatives. We describe here production purification and characterization of novel  Lactobacillus pentosus for further properties on enhancement of food safety and shelf life of food products. LC/MS analysis techniques for the  quantitative profiling of bacteriocins present in the probiotic preparations of Lactobacillus pentosus. LC-MS/MS analysis techniques, data  analysis is novel in bacteriocin research and suitable for the comprehensive bioanalysis of diverse, low-abundant bacteriocins in complex  sample.
Keywords: Bacteriocin; Lactobacillus pentosus,; liquid chromatography- mass spectrometry (LCMS)